GERAKAN LITERASI MATEMATIKA ONE DAY ONE TOPIC UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL BERPIKIR TINGKAT TINGGI HOTS - Isti Hari Wahyuni; Fitroh, Rokhimatul; Iesyah Rodliyah (Discovery : Jurnal Ilmu Pengetahuan, 2023)
The aim of this research is to determine the impact of the one day one topic mathematical literacy movement on students in solving HOTS questions on circle material. This research uses a qualitative type of research, with a qualitative descriptive approach. The data collection techniques used were written tests, interviews and documentation. The research subjects were all class 8A students at SMPN 01 Jombang who were then taken by two students for interviews. This research uses five basic mathematical literacy skills, namely communication skills, mathematization, determining strategies for solving problems, using operations and symbol language, formal language and technical language, as well as reasoning and giving reasons. The results of the research show that students with high academic abilities are able to use the five basic skills of mathematical literacy in solving HOTS questions on circle material, while students with moderate academic abilities are able to use the five basic literacy skills in working on HOTS questions on circle material in the evaluation aspect. However, based on interviews, students with moderate abilities still need further training in mathematical literacy for strategic skills in solving problems.